Conspiracy Theories and Modern Disjuncture Amidst COVID-19 in Indonesia - Ibnu Nadzir (Masyarakat Indonesia, 2020)
Amidst the global outbreak of COVID-19 in Indonesia, the government has been under the spotlight for not being able to formulate a proper response. Aside from the malfunctioning bureaucracy, the low compliance among Indonesian citizen toward public health advice complicates the impact of COVID-19 in Indonesia. One factor that contributes to the attitude of society is the spread of false information and conspiracy theories associated to the virus itself. How do we explain the spread of conspiracy theories propagation under the threat of COVID-19 in Indonesia? The article argues that the spread of conspiracy theories amidst the pandemic reflects the on-going contestation of political legitimacy between state and society in Indonesia. To elaborate this point, the article elucidates the three critical junctures that buttressed the propagation of conspiracy theories. First, conspiracy theory was utilized as a foundation of authoritarian regime of Soeharto, and later became an institutionalized tool to maintain its power. Second, the entanglement between democratic ecosystem and proliferation of social media after Reformasi has enabled society to appropriate conspiracy theories as a form of resistance and skepticism toward government. Third, the tension between state and society in regards to the authority manifested on the contention on COVID-19 management in Indonesia. The government have been trying to maintain the legitimacy by being secretive on COVID-19 information. At the same time, some elements of society responded to the secretive government with propagation conspiracy theories that also justify public disobedience toward health protocols. These combinations have further exacerbated the impact of COVID-19 in Indonesia.